Caste, Sex, and Parasitism Influence Brain Plasticity in a Social Wasp - Gandia, Kristine M.; Cappa, Federico; Baracchi, David; Hauber, Mark. E.; Beani, Laura; Uy, Floria M. K. (Frontiers in Ecology and Evolution, 2022)
Brain plasticity is widespread in nature, as it enables adaptive responses to sensory demands associated with novel stimuli, environmental changes and social conditions. Social Hymenoptera are particularly well-suited to study neuroplasticity, because the division of labor amongst females and the different life histories of males and females are associated with specific sensory needs. Here, we take advantage of the social wasp Polistes dominula to explore if brain plasticity is influenced by caste and sex, and the exploitation by the strepsipteran parasite Xenos vesparum. Within sexes, male wasps had proportionally larger optic lobes, while females, regardless of caste, had larger antennal lobes, which is consistent with the sensory needs of sex-specific life histories. Within castes, reproductive females had larger mushroom body calyces, as predicted by their sensory needs for extensive within-colony interactions and winter aggregations, than workers who frequently forage for nest material and prey. Parasites had different effects on female and male hosts. Contrary to our predictions, female workers were castrated and behaviorally manipulated by female or male parasites, but only showed moderate differences in brain tissue allocation compared to non-parasitized workers. Parasitized males maintained their reproductive apparatus and sexual behavior. However, they had small brains and large sensory brain regions than non-parasitized males. Our findings confirm that caste and sex mediate brain plasticity in P. dominula, and that parasitic manipulation drives differential allocation of brain regions depending on host sex.